INFLUENCE OF PERFORMANCE MANAGEMENT PRACTICES ON PERFORMANCE CONTRACTING OUTCOMES IN KENYA: A CASE OF MINISTRY OF EDUCATION, SCIENCE AND TECHNOLOGY - Odeka, Obure Clement; Minja, Prof. David; Kiruthu, Dr. Felix (Journal of Public Policy and Administration, 2017)
Purpose: The purpose of this study was to investigate the influence of performance management practices on performance contracting outcomes in the Ministry of Education, Science and Technology Methodology: The study employed a descriptive case study research design. The target population consisted of all the 600 employees in all cadres of members of staff in the Ministry of Education, Science and Technology that were based in the headquarters. In this study, a sample of 15% of the total population was used. Primary data was collected using structured questionnaires. Data analysis was conducted using statistical package for social sciences (SPSS) computer software. Results: The study findings revealed that staff development, work planning, strategic planning and financial resource allocation had positive and significant effects on performance contracting outcomes in the ministry. Unique contribution to theory, practice and policy: It was recommended that the ministry had to undertake quality and continuous training on performance contracting for those individuals actively involved in the process. Adequate funds for the training needed to be provided in the budget always and that capacity building needed to be embraced as a common practice in the ministry. It was also recommended that work plans needed to be circulated to all departments and also made available to the various teams implementing the performance contracts. The study further recommended that the ministry's strategic plans needed to be comprehensive and have clearly spelt out intentions to guide the implementation of the set goals. Avenues needed to be made available to ensure that all employees are involved in the process of strategic planning.